Термодинамічний аналіз систем комбінованого виробництва теплоти та холоду - Dubovskoy S.V.; Tverdohlib A.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
At the present time, the use of combined heat and cold generation systems is developing worldwide and is adopted in many countries of the world. To estimate the competitiveness of such systems, a detailed analysis based on the indicators characterizing the operating energy specific costs for the heat and cold generation is required.Calculation of these indicators is based on the exergy method, which provides the possibility of sharing operating energy costs proportionally to the exergy of products, based on the assumption of equality of heat and cold exergy efficiency processes, which has no scientific grounds.This paper presents a new method of sharing costs for heat and cold generation under the combined production conditions, according to the first and second laws of thermodynamics, which is free from the above mentioned assumption. This method allows sharing costs for heat and cold generation and the definition of heat and cold generation efficiency indicators, which are unequal to one another.It is shown that exergy losses in such combined processes should be shared proportionally to the exergy temperature functions of products. The methodological calculations are exemplified by the quantitative comparison of the proposed thermodynamic method and the exergy method of sharing costs in the systems of combined heat and cold generation based upon the piston refrigeration units. In the case under consideration the exergy method is proven to underestimate the efficiency of heat generation and overestimate the efficiency of cold generation by 2... 24 percent depending on the degree of inconvertibility of combined processes.